Pendidikan Islam Multikultural dalam Pembentukan Karakter Islami: Telaah Kritis atas Fenomena Intoleransi Peserta Didik - Hilmy Alwy Abdillah (UIN Fatmawati Sukarno Bengkulu, 2026)
Multicultural Islamic education is conceptually positioned as a strategic approach to fostering Islamic character marked by tolerance, inclusivity, and ethical conduct among students. However, persistent cases of intolerance and exclusivist behavior in schools raise critical questions regarding the effectiveness of multicultural Islamic education in educational practice.This study employs a qualitative approach using a literature review method. Data were collected through critical analysis of scholarly books, journal articles, and relevant publications addressing multicultural Islamic education, Islamic character formation, and student intolerance. Data analysis was conducted thematically to identify patterns, trends, and gaps between theoretical concepts and educational practices.The findings indicate that multicultural Islamic education has not been optimally effective in shaping students’ Islamic character due to its predominantly formalistic and normative implementation. Weak pedagogical internalization and limited institutional policy support reduce its transformative impact within the educational environment. Multicultural Islamic education remains relevant for Islamic character development but requires revitalization through reflective pedagogy, contextual value internalization, and institutional integration into school policies and culture to effectively address student intolerance.